„Pagal karo teisę ir papročius“: sutartys ir karo belaisviai XIV–XV amžiuose - Petrilionis, Antanas (Vilnius University Open Series, 2024)
The law of war in the Middle Ages extended beyond the considerations of when to initiate a war (the concept of ius belli), the treatment of prisoners, and the permissibility of plunder and destruction. These dimensions were shaped by the contributions of medieval jurists and, significantly, by the influence of Christianity. Despite the concerted efforts to regulate warfare, certain practices persisted, such as the capture of peasants, women, and children – the non-combatants. The expansion of Christianity to the East, particularly to the Baltic Sea region, saw these principles advancing hand in hand, especially through the Teutonic Order and Western nobility. This article endeavors to analyze, primarily drawing from normative sources, the criteria for becoming a prisoner of war during the conflicts involving the Teutonic Order, the Grand Duchy of Lithuania, and the Kingdom of Poland in the fourteenth and fifteenth centuries. It explores the process of prisoner distribution and examines the prevailing customs and rules outlined in treaties. Notably, the peace treaties of Salynas (1398), Thorn (1411), Melno (1422), and Brest (1435) highlight evolving formulations in the quest to define who qualified as a “prisoner of war,” the conditions for regaining freedom, and the challenges surrounding the effectiveness of international treaties on the matter of captives.
Keywords: karo teisė; karo belaisviai; Vokiečių ordinas; LDK; Viduramžiai